An Achievement of Project Analysis and Project Management Titled Project Feasibility Study Through Using Peer Assisted Learning.: ผลสัมฤทธิ์ทางการเรียนรายวิชาการวิเคราะห์โครงการและการบริหารโครงการ เรื่อง การศึกษาความเป็นไปได้ของโครงการ โดยวิธีการจัดการเรียนรู้แบบเพื่อนช่วยเพื่อน - ทีดี ธัชพล (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2018)
The purpose of this research was to study learning achievement after using peer learning method, Project Analysis and Management course in the topic of Feasibility Study by using peer learning. The research samples were 2 students of students group 581947003C that had enrolled in PA 2208301 course, Project Analysis and Management 2 semester of academic year 2560 by using purposive sampling method which has selection criteria as the students who with a pre-test score less than 50 percent. Tools used in the study include pretest, posttest and the study management plan for peer learning. Data analysis using the method of percentage mean and One sample t-test The study result had shown that learning achievement of the pretest and posttest score found that the average score of posttest was higher than pretest score (=12.50) and the percentage was 62.50 as wall as .707 standard deviation. The statistical significance was .05 while the difference of pretest score and posttest score was 6.50. These results shown that studying by peer learning method cause the learning achievement of students in post-course higher than pre-course. The students had had join in every activity, shared opinion together, take care and explain the tasks or lessons together, students ask questions when there were problems or doubts in the activities or lessons. Also, students had fun in learning, be intimate with each other and building good relationships between friends and teachers